1985
DOI: 10.1080/03601238509372502
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytochrome p‐450 and phosphatidylcholine synthesis by endosulfan in liver of rats : Effect of quality of dietary proteins

Abstract: Administration of endosulfan significantly increased microsomal protein, cytochrome P-450 content and the activity of aminopyrine N-demethylase. Effect of endosulfan and actinomycin D either alone or together on microsomal protein, cytochrome P-450, NADPH cytochrome c reductase, aniline hydroxylase, aminopyrine N-demethylase, phosphatidylcholine content, incorporation of 3H-choline and 14C-methionine were studied in rats given amino acid deficient and supplemented diets. Administration of endosulfan significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In both mammals (Gupta & Gupta 1979, Tyagi et al 1985 and fish (Jensen et al 1991) endosulfan has been shown to function as a phenobarbital-type inducer of cytochrome P-450. In general, fish have repeatedly been shown not to respond to induction by phenobarbital-type compounds ( G o k s~y r et al 1987, Kleinow et al 1987, Gooch et al 1989, Winston et al 1989), although they express corresponding cytochrome P-450 IIB genes (Elskus & Stegeman 1989, Stegeman 1989, Miranda et al 1990; for nomenclature, see Nebert et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In both mammals (Gupta & Gupta 1979, Tyagi et al 1985 and fish (Jensen et al 1991) endosulfan has been shown to function as a phenobarbital-type inducer of cytochrome P-450. In general, fish have repeatedly been shown not to respond to induction by phenobarbital-type compounds ( G o k s~y r et al 1987, Kleinow et al 1987, Gooch et al 1989, Winston et al 1989), although they express corresponding cytochrome P-450 IIB genes (Elskus & Stegeman 1989, Stegeman 1989, Miranda et al 1990; for nomenclature, see Nebert et al 1991).…”
Section: Introductionmentioning
confidence: 99%